A One-Year Introductory Biology Majors’ Lab Sequence Incorporating Vision & Change - Merrilee F. Guenther (American Society for Microbiology, 2019)
The introduction of Vision and Change by AAAS and the recommendation that biology departments amend their curricula to focus on key concepts and skills necessary for graduates have led to a re-envisioning of introductory curricula across the nation. Many of the “standard” biology text books have realigned their focus with Vision and Change, while new texts have emerged that completely revise how we teach introductory biology majors. One such textbook is Integrating Concepts in Biology (ICB), by Campbell, Heyer, and Paradise. Many departments, including ours, have adopted this text as a novel way to teach biology majors, focusing on active learning, the scientific method, and specifically, understanding data. However, with all of these revisions to biology textbooks, there have been no revisions or insights into corresponding labs for a typical 1-year introductory course sequence. Here, we provide a description of our 1-year lab sequence, emphasizing the scientific method and novel research, with a focus on the five “Big Ideas” presented in ICB. By removing the “cookbook” labs typical of most introductory laboratory courses, we found that this system better emphasized the focus of Vision and Change and, concomitantly, student appeared to enjoy the lab sequence and see the relevance to class material better, compared to previous years. We believe that this lab organization is a simple design that is not resource-intensive and can be utilized at schools of any size or budget.